EL DIAGRAMA CIRCULAR PARA LA FORMACION DE PROFESIONALES AGRICOLAS EN LA FACULTAD DE CIENCIAS AGRARIAS DE LA UNIVERSIDAD DE GUAYAQUIL CON CAPACIDAD PARA REALIZAR UNA AGRICULTURA RENTABLE, COMPETITIVA, AGROINDUSTRIAL Y SOSTENIBLE. LINEAMIENTOS ALTERNATIVOS. - JOHNS RODRIGUEZ ALAVA (2004)
THE CIRCULAR DIAGRAM FOR THE TRAINING OF AGRICULTURAL PROFESSIONALS IN THE FACULTY OF AGRICULTURAL SCIENCES OF THE UNIVERSITY OF GUAYAQUIL WITH THE ABILITY TO CARRY OUT PROFITABLE, COMPETITIVE, AGRIBUSINESS AND SUSTAINABLE AGRICULTURE. ALTERNATIVE GUIDELINES.